Clinical Outcomes of Posterolateral Complex Reconstruction Performed with a Single Femoral Tunnel - Helito, Camilo Partezani; Sobrado, Marcel Faraco; Giglio, Pedro Nogueira; Bonadio, Marcelo Batista; Pécora, José Ricardo; Gobbi, Riccardo Gomes; Camanho, Gilberto Luis; Angelini, Fabio Janson (The Journal of Knee Surgery, 2019)
The objective of this study is to report the functional outcomes, complications, and reconstruction failure rate of patients undergoing posterolateral complex reconstruction with a single femoral tunnel technique. Patients with posterolateral complex injuries associated with injury of the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), or both undergoing surgical treatment with the single femoral tunnel technique were included in the study. The International Knee Documentation Committee (IKDC) and Lysholm's scales were evaluated, in addition to age, gender, time between trauma and surgery, trauma type, range of motion (ROM) restrictions, peroneal nerve injury, and reconstruction failure. Sixty-six patients were included. Eighteen underwent ACL and posterolateral complex (PLC) reconstruction (group 1), 24 underwent ACL, PCL, and PLC reconstruction (group 2), and 24 underwent PCL and PLC reconstruction (group 3). The mean follow-up was 63 months. The subjective IKDC was 83.7 ± 14.6 for group 1, 74.3 ± 12.6 for group 2, and 66.3 ± 16.0 for group 3 (p < 0.001). The Lysholm's score was 87.1 ± 12.8 for group 1, 79.5 ± 15.0 for group 2, and 77.7 ± 15.2 for group 3 (p = 0.042). There were six reconstruction failures among the patients (9.1%) with no differences among the groups (p = 0.368). Female gender and reconstruction failure were associated with worse outcomes. Patients undergoing reconstruction of PLC structures with the single femoral tunnel technique achieved good functional outcomes and a failure rate similar to literature. Patients undergoing only combined ACL reconstruction showed better outcomes than patients undergoing combined PCL reconstruction. Female gender was associated with a worse functional outcome irrespective of the injury type.
Keywords: posterolateral complex; posterolateral corner; fibular (lateral) collateral ligament; multiligament; chronic knee injury